Defense of Cultural Values of the Jejuluk Pernicir Kabayan Tradition in Ulak Kapal Village, Ogan Komering Ilir (Literary Anthropology Study) - Yanti Yanti; Yessi Fitriani; Puspa Indah Utami (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aimed to understand how the community of Ulak Kapal Village maintains the cultural values embedded within the endangered kabayan marriage tradition amidst social change. A qualitative case study approach was employed. Data were collected through in-depth interviews, participatory observation, and analysis of community documents. The community preserves the tradition through intergenerational education, active community participation, and the strategic use of technology. Analysis revealed the tradition embodies five key literary anthropology values: language, systems of knowledge and communication, technology and equipment, livelihood systems, and art all retaining relevance in modern life. The research provides a contemporary analysis of a specific, lesser-documented marital tradition, uniquely applying the framework of literary anthropology to deconstruct its enduring cultural values and active preservation mechanisms. The findings offer a replicable model for safeguarding intangible cultural heritage, demonstrating how communities can synergize traditional education, social participation, and modern technology to sustain cultural practices. The study contributes to cultural preservation theory by documenting a living tradition and its adaptive strategies, offering valuable insights for anthropologists and policymakers focused on sustaining cultural diversity in evolving societies.